2012
DOI: 10.1007/s10750-012-1090-4
|View full text |Cite
|
Sign up to set email alerts
|

Composition and structure of macroinvertebrate communities in contrasting open-water habitats in Irish peatlands: implications for biodiversity conservation

Abstract: The purpose of this study was to consider the relative importance of several habitat variables in explaining the patterns in the structure of macroinvertebrate assemblages in open-water habitats, in relatively intact bogs and fens, which should inform conservation strategies. It was hypothesised that variables relating to the size of the water body would differentiate the communities and that some species would be unique to certain conditions. The macroinvertebrate communities from pools [100 m 2 , 10.1-100 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Most recorded taxa adapted to tolerate fluctuating environments, due to a variety of physiological features and biological traits (e.g. flexible life cycles, body size, dispersal mechanism) that allow them a successful colonization, dispersion and survival in temporary waters (Williams 2006;Jeffries 2011;Hannigan and Kelly-Quinn 2012). Accordingly, in Mallín Crespo, only a few invertebrates survived the harshest period (Corynoneura sp., Lymnaea sp., Ostracoda, Aulodrilus limnobius and Podonominae sp.2), imposed by winter temperatures and water flow ( Figure 6).…”
Section: Invertebrate Biodiversity and Assemblagesmentioning
confidence: 99%
“…Most recorded taxa adapted to tolerate fluctuating environments, due to a variety of physiological features and biological traits (e.g. flexible life cycles, body size, dispersal mechanism) that allow them a successful colonization, dispersion and survival in temporary waters (Williams 2006;Jeffries 2011;Hannigan and Kelly-Quinn 2012). Accordingly, in Mallín Crespo, only a few invertebrates survived the harshest period (Corynoneura sp., Lymnaea sp., Ostracoda, Aulodrilus limnobius and Podonominae sp.2), imposed by winter temperatures and water flow ( Figure 6).…”
Section: Invertebrate Biodiversity and Assemblagesmentioning
confidence: 99%
“…Even though the conservation values of bogs have been internationally recognized, these wildlife habitats are still understudied in comparison to most other freshwater habitats (Baars et al 2014). Recent studies have shown that peat bogs are inhabited by unique macroinvertebrate assemblages, often containing rare and threatened species (Hannigan and Kelly-Quinn 2012, Drinan et al 2013, Baars et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a number of invertebrate species or assemblages have been used or proposed as peatland biodiversity indicators, including carnivorous ground beetles (Williams et al, 2014), hoverflies (Speight et al, 2002) and aquatic macroinvertebrates (Hannigan & Kelly-Quinn, 2012).…”
Section: Introductionmentioning
confidence: 99%